Prevalence of cataract among Australian commercial airline pilots. Issue 1 (2nd January 2023) - Miura, Kyoko; Coroneo, Minas; Dusingize, Jean Claude; Olsen, Catherine M.; Tinker, Rick; Karipidis, Ken; Hosegood, Ian; Green, Adèle C.
Abstract: Because little is known about cataract in pilots, we estimated prevalence by anonymously ascertaining all commercial airline pilots diagnosed with cataract 2011–2016 using the electronic Medical Records System of the Australian Civil Aviation Safety Authority. Of 14, 163 Australian male commercial pilots licensed in 2011, 1286 aged ≥60 had biennial eye examinations showing a cataract prevalence of 11.6%. Among 12, 877 pilots aged <60, based on compulsory eye examinations only when first licensed, prevalence was 0.5%. There was no significant difference by ambient ultraviolet (UV) radiation levels in state of residence though lowest prevalence was seen in the low-UV state of Victoria. Most cataract in pilots ≥60 years was bilateral and of mild severity, while cataract in pilots <60 were more likely to be unilateral and of greater severity.